Kesulitan Guru IPA Kelas VIII dalam Merencanakan dan Melaksanakan Asesmen - Rifki Dimastian; Rini Rita T. Marpaung; Berti Yolida (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2017)
This research aimed to gain the difficulty of science teachers in planning and implementation the assessment. The difficulties of science teachers in planning and implementation the assessment were affective, cognitive, and psychomotoric. The research's sample were science teachers of VIII grade in Teluk Betung Utara. Descriptive design was applied in this research. The writer collected the data from questionnaire and interview. The result of these questionnaires showed the difficulty of science teachers in planning the assessment that classified as moderate in determining the aim of assessment indicator, arranging the instrument and latticework, writing the question based on latticework and guideline of writing a question, determining the criteria of quality question, and arranging suspension guidelines. The difficulty of science teachers in implementing the assessment was classified as moderate of assessment implementing indicator of affective, cognitive, and psychomotoric. Conclusion in this research that were teachers difficulty in planning and implementation the asssessment could be classified as moderate criteria.Tujuan penelitian ini adalah untuk mengetahui kesulitan guru IPA dalam merencanakan dan melaksanakan asesmen. Kesulitan guru IPA dalam merencanakan dan melaksanakan asesmen yaitu ketiga ranah afektif, kognitif, dan psikomotorik. Sampel pada penelitian ini menggunakan sampel jenuh yakni semua guru IPA kelas VIII di SMP Negeri se-Kecamatan Teluk Betung Utara. Desain pada penelitian ini adalah desain deskriptif. Analisis data kualitatif diperoleh dari hasil angket dan wawancara. Hasil penelitian menunjukkan kesulitan guru IPA dalam merencanakan asesmen tergolong kriteria cukup pada indikator menetapkan tujuan asesmen, menyusun instrumen, menyusun kisi-kisi soal, menulis soal berdasarkan kisi-kisi dan kaidah penulisan soal, menentukan kriteria mutu soal, serta menyusun pedoman penskoran. Kesulitan guru IPA dalam melaksanakan asesmen tergolong kriteria cukup pada indikator pelaksanaan asesmen ranah afektif, kognitif, dan psikomotorik. Kesimpulan dalam penelitian ini yaitu kesulitan guru dalam merencanakan dan melaksanakan asesmen termasuk dalam kriteria cukup.Kata kunci: asesmen, guru IPA, kesulitan, melaksanakan, merencanakan